The Relationship Of Knowledge And Defection Habits With Healthy Latrine Ownership In The Working Area Of Puskesmas Lempur, Kerinci Regency, 2023 - Umi Fathonah; Willia Novita Eka Rini; Fajrina Hidayati; Muhammad Syukri; Fitria Eka Putri (Pusat Riset dan Inovasi Nasional, 2024)
Healthy environmental sanitation is related to the ownership of healthy latrines in each house. In the lempur health center working area, 66.26% have access to healthy latrines. The target of healthy latrine ownership in the Lempur Health Center Working Area is 100%. TThis research aims to determine the relationship between knowledge and defecation habits in the work area of the Lempur Community Health Center, Kerinci Regency in 2023. Type of quantitative research with a cross sectional design, using questionnaire instruments and observation sheets with interview and observation methods. The research sample was 100 respondents in the working area of the lempur health center. The results of this study of 100 respondents there are 68% who do not meet the requirements of healthy latrines and there are 22% meet the requirements of healthy latrines. There is a relationship between the variables Knowledge, defecation habits, which are significantly related to the ownership of healthy latrines in the Lempur Community Health Center Working Area, Kerinci Regency. The public is advised to be aware of the importance of using good and healthy latrines